Meningkatkan Pemahaman Konseptual dan Keterampilan Praktis Instalasi Listrik Melalui Model Pembelajaran Berbasis Proyek - Jesika Putri Samosir; I Gede Ratnaya; I Komang Gede Sukawijana (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving vocational students’ conceptual understanding and practical skills in the subject of electrical installation. The research was motivated by students’ limited ability to connect theoretical concepts with real-world applications, which has resulted in suboptimal learning outcomes. A quantitative approach with a quasi-experimental non-equivalent control group design was employed, involving two groups: an experimental class that received instruction using the PjBL model and a control class that was taught through conventional methods. Research instruments included a conceptual understanding test, a practical skills observation sheet, and a student response questionnaire. Data were analyzed using the t-test to examine differences between the two groups. The findings reveal that the implementation of PjBL has a significant positive effect on enhancing students’ conceptual understanding and practical skills compared to conventional learning. Therefore, the PjBL model is proven to be effective in strengthening both theoretical mastery and technical competencies among vocational students, and it is highly relevant for improving the quality of learning in electrical engineering education.